Prevalence and Antimicrobial Susceptibility Profile of Salmonella from Poultry Farms and In-Contact Humans and Associated Risk Factors in Addis Ababa, Ethiopia - Aberaw Akalu; Tekalign Tadesse; Haile Alemayehu; Girmay Medhin; Desalegn Woldeyohannes; Tadesse Eguale (International Journal of Microbiology)
Poultry and poultry products are the common sources of Salmonella,which is one of the serious food-borne bacterial diseases in humans. Little is known about the status of Salmonella and their antimicrobial susceptibility in poultry farms in Addis Ababa. This study was conducted to estimate the prevalence and antimicrobial susceptibility of Salmonella isolates and to investigate possible risk factors for the occurrence of Salmonella in poultry farms in Addis Ababa. We recruited 58 poultry farms, from which 471 poultry-related samples and 44 stool samples from in-contact humans were collected. The isolates were tested for their susceptibility to 11 antimicrobials using the Kirby–Bauer disk diffusion assay. The farm-level prevalence of Salmonella was 36.2% and the sample-level prevalence was 6.4% for samples taken from poultry farms and 4.5% in human stool samples who have contact with poultry. On-farm waste disposal practices and chicken being purchased from different multiplication farms were significantly associated with Salmonella positivity of the farms (p<0.05). Eleven (34.4%) Salmonella isolates were resistant to streptomycin, and nine (28.1%) were resistant to tetracycline. Thirteen (40.6%) Salmonella isolates were resistant to two or more antimicrobials tested in this study, whereas resistance to 3 or more antimicrobials was detected in seven (21.9%) isolates. In conclusion, a high prevalence of Salmonella and a high rate of resistance to multiple antimicrobials were detected in poultry farms in Addis Ababa. Hence, implementation of strong biosecurity measures and rational use of antimicrobials are recommended.